EVALUATION OF THE SARS-COV-2 DETECTION PROCESS ON THE ABBOTT AUTOMATIC SYSTEM m2000RT - Nguyen Duy Thái; Vu Duy Dung; Tran Hong Tram; Vu Thi Lan Anh; Do Thi Huong; Dang Anh Ngoc; Vuong Thi Mai Linh; Doan Huu Xuyen (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2023)
Amidst the complex progression of the COVID-19 pandemic in Vietnam, in response to the need for diagnosing suspected COVID-19 patients, we conducted research to validate the procedure for detecting the SARS-CoV-2 virus on the Abbott m2000 system using real-time PCR. We used a positive control sample (Abbott Real Time SARS-CoV-2 Positive control provided by the manufacturer) to assess the accuracy and Limit of Detection (LOD) of the procedure. The results indicated that the detection limit of the method met the manufacturer's recommendation with a test sample concentration of 100 copies/ml and a 100% positivity rate. The accuracy, encompassing both specificity and sensitivity, was 100% with community-collected test samples having a concentration ≥100 copies/ml. Our study has proven that the detection procedure for the SARS-CoV-2 coronavirus on the Real-Time PCR m2000 system meets the accuracy and detection limit criteria set by the manufacturer. Based on these research findings, there's a scientific basis to apply this procedure for diagnostic testing of the SARS-CoV-2 coronavirus in samples at the National Institute for Control of Vaccine and Biologicals (NICVB).